GuaB activity is required in Rhizobium tropici during the early stages of nodulation of determinate nodules but is dispensable for the sinorhizobium meliloti-alfalfa symbiotic interaction - Collavino, Mónica Mariana (2005)
The guaB mutant strain Rhizobium tropici CIAT8999-10T is defective in symbiosis with common bean, forming nodules that lack rhizobial content. In order to investigate the timing of the guaB requirement during the nodule formation on the host common bean by the strain CIAT899-10.T, we constructed gene fusions in which the guaB gene is expressed under the control of the symbiotic promoters nodA, bacA, and nifH. Our data indicated that the guaB is required from the early stages of nodulation because full recovery of the wild-type phenotype was accomplished by the nodA-guaB fusion. In addition, we have constructed a guaB mutant derived from Sinorhizobium meliloti 1021, and shown that, unlike R. tropici, the guaB S. meliloti mutant is auxotrophic for guanine and induces wild-type nodules on alfalfa and Medicago truncatula. The guaB R. tropici mutant also is defective in its symbiosis with Macroptilium atropurpureum and Vigna unguiculata but normal with Leucaena leucocephala. These results show that the requirement of the rhizobial guaB for symbiosis is found to be associated with host plants that form determinate type of nodules.